ANALISIS KELAIKAN FUNGSI JALAN PADA RUAS JALAN BUNDARAN PESAWAT KE LAMPU MERAH PASAR BARU - Soeparyanto, Try Sugiyarto; Syah Nuhun, Ridwan; Alamsyah, Sahrul; Minsi, Salfin Hartani; Dzariat, La ode (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
The purpose of this study is to analyze the feasibility of road functions on the Airplane Roundabout Road to Pasar Baru Red Light. The data analysis in this study is ULFJ analysis and Road Function Feasibility Administration Analysis. The research results indicate that (1) the analysis of ULFJ, overall the section from Bundaran Pesawat to Lampu Merah Pasar Baru falls into the category of